2016
DOI: 10.4103/ijmr.ijmr_1078_14
|View full text |Cite
|
Sign up to set email alerts
|

Protection against osteoarthritis in experimental animals by nanogold conjugated snake venom protein toxin gold nanoparticle-Naja kaouthia cytotoxin 1

Abstract: Background & objectives:Increased severity of osteoarthritis (OA) and adverse side effects of its treatment led to the search for alternative therapies. It was previously reported that snake venom protein toxin Naja kaouthia cytotoxin 1 (NKCT1) and gold nanoparticle (GNP) individually have potential against excremental arthritis. In this study, we analyzed the protective activity of GNP conjugated protein toxin NKCT1 (GNP-NKCT1) against experimental OA.Methods:Gold nanoparticle conjugation with NKCT1 (GNP-NKCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Another study also indicated that AuNPs in the form of complexes bound to VEGF to treat RA (Lee et al, 2014). Furthermore, AuNPs could down-regulate proinflammatory responses and consequently inhibit inflammation both in OA and RA (Gomes et al, 2016;Gul et al, 2018). And the protection of AuNPs for ECM of which the degradation is related to OA and RA have been proved.…”
Section: The Protection For Cartilage Tissuementioning
confidence: 98%
“…Another study also indicated that AuNPs in the form of complexes bound to VEGF to treat RA (Lee et al, 2014). Furthermore, AuNPs could down-regulate proinflammatory responses and consequently inhibit inflammation both in OA and RA (Gomes et al, 2016;Gul et al, 2018). And the protection of AuNPs for ECM of which the degradation is related to OA and RA have been proved.…”
Section: The Protection For Cartilage Tissuementioning
confidence: 98%
“…60 Other studies reported the evidence of antiapoptotic role of nanoparticles. 61 Our results clearly indicated less pro-apoptotic activity in GNPs treated hADMSCs, caspase-3 (0.734 ± 0.13) and BAX (0.830 ± 0.12) as compared to the stress/MIA (1.68 ± 0.12) group (Figure 10). Contrarily, the BCL-2 (1.978 ± 0.155) gene expression is high in the GNPs treated group that is in accordance with other studies.…”
Section: Gnps Decreased Apoptosis and Improved Cell Survivalmentioning
confidence: 55%
“…Contrarily, the BCL-2 (1.978 ± 0.155) gene expression is high in the GNPs treated group that is in accordance with other studies. 61 GNPs clearly showed the apoptotic activity against the cervical, lung, and breast cancer cell lines and do not affect the normal cells. 62 GNPs used in the respective study did not show any cytotoxic activity and, also found to act as anti-inflammatory agent by controlling the apoptosis markers to alleviate the inflammation.…”
Section: Gnps Decreased Apoptosis and Improved Cell Survivalmentioning
confidence: 98%
“…Further correlation of acute inflamed joints is agreeable in the synovial fluids containing high level of PLA2 in patients with rheumatoid arthritis [158]. The protective activity of nanogold conjugated with snake venom protein toxin, NKCT1 N. kaouthia, against osteoarthritis in albino Wistar rats by limiting the inflammatory markers at the molecular level has been reported [159]. The experiment provides evidence of metalloproteinase BaP1 from B. asper has pro-nociceptive activity in joints.…”
Section: Arthritismentioning
confidence: 89%